Checkpoint inhibitor is active against large cell neuroendocrine carcinoma with high tumor mutation burden. Issue 1 (19th September 2017) - Wang, Victoria E.; Urisman, Anatoly; Albacker, Lee; Ali, Siraj; Miller, Vincent; Aggarwal, Rahul; Jablons, David
Abstract : Background: Large cell neuroendocrine tumor (LCNEC) of the lung is a rare and aggressive tumor similar to small cell lung cancer (SCLC). Thus, it is often treated similarly to SCLC in the front-line setting with a platinum doublet. However, treatment for patients beyond the first line remains undefined. Case presentation: We report the case of a patient with stage IB LCNEC (PD-L1 negative but positive for PD-L1 amplification and tumor mutation burden high) who progressed after adjuvant chemotherapy after surgery and subsequent therapy with an antibody drug conjugate targeting a neuroendocrine-specific cell surface marker but achieved a significant and durable response with pembrolizumab, a humanized IgG4 monoclonal anti-PD-1 antibody. Conclusions: Immunotherapy with checkpoint inhibitors is an effective treatment option for patients with metastatic LCNEC, even if PD-L1 expression is negative.